Correction of Double-Chambered Right Ventricle 40 Years after Pulmonary Valvuloplasty - Elmar W. Kuhn; Gerardus Bennink; Thorsten Wahlers; Jens Wippermann (The Thoracic & Cardiovascular Surgeon Reports, 2015)
Abstract